2020
DOI: 10.1177/2633494120941480
|View full text |Cite
|
Sign up to set email alerts
|

Update on the management of poor ovarian response in IVF: the shift from Bologna criteria to the Poseidon concept

Abstract: Despite the considerate progress to which assisted reproduction technology (ART) has been subject since 1978, some issues remain unresolved. Notably, the clinical management of patients with a poor ovarian response is still a challenge in everyday practice, frustrating to both the patient and the fertility expert. Poor ovarian responders (PORs) embody 9–24% of patients undergoing ovarian stimulation, meaning that up to one in four patients conceals a poor reproductive prognosis. The last decade has witnessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 93 publications
(116 reference statements)
0
35
0
1
Order By: Relevance
“…There are indications that lifestyle modifications with weight loss prior to assisted reproductive technologies (ART) show benefits compared to immediate treatment in obese women with PCOS [5]. Yet, ART is a promising option 2 of 17 with suitable interventions for the clinical management of infertility, including in vitrofertilization (IVF) and intracytoplasmic sperm injection (ICSI) [6]. With a steadily rising demand over the past decades, it is essential to understand which factors may optimize the outcome of ART treatment, as live birth rate (LBR) is still observed in around 36% to 50% of attempts only [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There are indications that lifestyle modifications with weight loss prior to assisted reproductive technologies (ART) show benefits compared to immediate treatment in obese women with PCOS [5]. Yet, ART is a promising option 2 of 17 with suitable interventions for the clinical management of infertility, including in vitrofertilization (IVF) and intracytoplasmic sperm injection (ICSI) [6]. With a steadily rising demand over the past decades, it is essential to understand which factors may optimize the outcome of ART treatment, as live birth rate (LBR) is still observed in around 36% to 50% of attempts only [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The current popular view for classification is the Poseidon Criteria 17 which seek to stratify significantly more homogeneous subpopulations taking age, ovarian reserve and previous ovarian response after stimulation with gonadotrophins into account. This has led to the distinguishing of at least four groups with suggestions for different treatments for each subgroup 18 (see Figure 1 ).…”
Section: Definition Of Poor Respondersmentioning
confidence: 99%
“…In such cases, maximizing the oocyte yield can lead to higher cumulative birth rates. However, optimal treatment options should be considered [ 11 ]. In contrast, some clinical trials showed that needling women with diminished ovarian reserves at multiple acupoints could yield positive outcomes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%